Study guides

☆☆

Q: What is the answer to -8 plus 7 multiply 6x plus 3 equals -7x-5-1?

Write your answer...

Submit

Related questions

y = -6x + 3 Multiply the slope by the negative reciprocal y = 1/6x + 3

Multiply the first by 3 and the second by -2

you multiply it

-6x

6x+x = 7x

(9,6)

6x plus 3 equals 8x plus 14 when solved mathematically is equal to x = -5.5.

6x

x=10

6x+4=52 6x=48 x=8

The quadratic expression x2+6x+8 when factorised equals (x+2)(x+4)

6x plus 3y minus 2x plus 5y equals 4x plus 8y.

5x + x - 6x + 2x = 2x

144

(9,2)

y=(6x-5)/3

6x+7 = -56x = -12x = -2

234 it is not the answer

6

no

-6x

16x+9 without the rest of the equation, what this equals, I can't solve

It is: 3x2+6x-11 = 0

-6x + 20.4 = 48 -6x = 48 - 20.4 -6x = 27.6 x = -4.6

-6x + y = 9 (+6x) -> y = 6x + 9